Virtual Reality Applications in the Construction Industry - Attallah, Sherif O; Oev, Firuz; Mahfouz, Tarek (IJRDO-Journal of Applied Science, 2018)
The purpose of this paper is to give an overview of Virtual Reality also known as VR to the reader including the history of its development, the technological solutions offered by adapting to VR, , how virtual reality is achieved and why it is used. The paper will also cover the different applications that the VR technology is currently most popular in, future trends and advancements of the VR world. This paper will then cover the different ways Virtual Reality is being used in the construction industry. Finally, the ways the construction industry is being transformed and benefits from adapting to VR in safety solutions and in education will be discussed.